DEIKSIS PERCAKAPAN DALAM INSTRAGRAM elelrumi DAN syifahadju - Resti, Fitri; Nanda Risky Ardhana (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Communication is a process that involves the exchange of information, facts, ideas and thoughts between individuals or groups. Communication can be done through various means, such as verbally, body movements, and electronic media. So, researchers try to find out about meaning in oral communication. This research aims to describe persona deixis on Elelrumi and Syifa Hadju's Instagram. The research created by researchers is a type of qualitative research. The research method used is descriptive qualitative. The data for this research are utterances in Elelrumi and Syifa Hadju's Instagram comments in the form of words containing persona deixis. Data collection techniques in this research are observation, documentation and data classification. The data analysis techniques used are data description, data analysis and data conclusions. Based on the results of the data analyzed, it can be concluded that Conversation Deixis in Elelrumi and Syifa Hadju's Instagram was found to be first and second person deixis. The first person deixis is Gue and Akuuhh. The second person deixis is el, mas el, cipaaa, sygku, Kiyowoooo Bayiekuuww, kakak, kamu, dan lo.